2014
DOI: 10.1371/journal.pone.0101521
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor MEF2C Negatively Controls Angiogenic Sprouting of Endothelial Cells Depending on Oxygen

Abstract: The MADS box transcription factor MEF2C has been detected by us to be upregulated by the angiogenic factors VEGF-A and bFGF in endothelial cells. We have here investigated its potential role for angiogenesis. MEF2C was surprisingly found to strongly inhibit angiogenic sprouting, whereas a dominant negative mutant rather induced sprouting. The factor mainly affected migratory processes of endothelial cells, but not proliferation. In gene profiling experiments we delineated the alpha-2-macroglobulin gene to be h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
3
9
0
Order By: Relevance
“…However, although loss of endothelial MEF2C had no detected effects in physiological conditions, Xu et al (2012) reported a significant increase in vascular recovery and a cognate decrease in pathological neovascularization in the Mef2C-null retinal vasculature after oxygen-induced retinopathy, indicating that loss of MEF2C results in increased sprouting after injury. These results, which correlate with work demonstrating reduced in vitro VEGFAinduced vascular sprouting after MEF2C overexpression (Sturtzel et al 2014), are in agreement with the consequences of Dll4 perturbations: Reduced DLL4 levels result in increased retinal vascular recovery and decreased neovascularizion after oxygen-induced retinopathy (Xu et al 2012) and increased sprouting in response to VEGFA (Sainson et al 2005;Jakobsson et al 2010), while overexpression of DLL4 reduces the in vitro responses to VEGFA (Williams et al 2006). Therefore, we hypothesize that even limited reductions of Dll4 levels downstream from MEF2C perturbation disrupt Notch-mediated lateral inhibition, resulting in hypersprouting in conditions of pathological stress.…”
Section: Discussionsupporting
confidence: 89%
“…However, although loss of endothelial MEF2C had no detected effects in physiological conditions, Xu et al (2012) reported a significant increase in vascular recovery and a cognate decrease in pathological neovascularization in the Mef2C-null retinal vasculature after oxygen-induced retinopathy, indicating that loss of MEF2C results in increased sprouting after injury. These results, which correlate with work demonstrating reduced in vitro VEGFAinduced vascular sprouting after MEF2C overexpression (Sturtzel et al 2014), are in agreement with the consequences of Dll4 perturbations: Reduced DLL4 levels result in increased retinal vascular recovery and decreased neovascularizion after oxygen-induced retinopathy (Xu et al 2012) and increased sprouting in response to VEGFA (Sainson et al 2005;Jakobsson et al 2010), while overexpression of DLL4 reduces the in vitro responses to VEGFA (Williams et al 2006). Therefore, we hypothesize that even limited reductions of Dll4 levels downstream from MEF2C perturbation disrupt Notch-mediated lateral inhibition, resulting in hypersprouting in conditions of pathological stress.…”
Section: Discussionsupporting
confidence: 89%
“…Knockdown of MEF2C in endothelial cells regulated endothelial cell survival and tube formation, further confirming the role of this transcription factor in the regulation of angiogenesis (Xu et al, ). Consistent with this, MEF2C was recently reported as a negative regulator of angiogenic sprouting of endothelial cells (Sturtzel et al, ).…”
supporting
confidence: 75%
“…MEF2C, which is regulated by let-7 g, has been Oncogenes BCL11A, BCL2L2, CBL, CCNA2, CCND1, CCND2, CCNE1, CHKA, CRK, CRKL, CSF1R, DEK, EIF5A2, ELK1, ERBB3, ERG, FGF2, FGFR1, FGFR3, FOS, GNAS, HMGA2, HOXA10, KRAS, LMO2, MAP3K8, MCF2, MYBL1, MYCL1, NET1, NRAS, PDGFRA, PIM1, PTPN11, RAF1, RALA, RUNX1T1, SALL4, SERTAD2, SET, SKI, TAF15, TAL1, TRIM32, USP6, WHSC1, ZNF217 Tumor suppressor genes ADAMTS18, AKAP12, APAF1, APC, ARHGAP20, ARHGAP35, ARHGEF12, ARID1A, ARID2, ARID3B, AXIN2, BACH2, BHLHE41, BLCAP, BTG2, CADM1, CADM4, CAMTA1, CBFA2T3, CDC73, CDKN1B, CDKN2A, CHEK1, CREBL2, CSMD1, CTDSPL reported as the main regulator in primary breast cancer (29). Mutations and deletions of this gene have been associated with severe mental retardation, stereotypic movement, epilepsy and cerebral malformation (30). MEF2A, regulated by miR-155, is involved in vertebrate skeletal muscle development and differentiation (31).…”
Section: Discussionmentioning
confidence: 99%